Experimental Study on Shear Strengths of Ice-Roof Interface Aiming the Study of Roof Snow Sliding - Cao, Xinli; Mo, Huamei; Zhang, Guolong; Zhang, Qingwen; Fan, Feng (Frontiers in Earth Science, 2022)
Sliding of roof snow is a threat to the structural safety of roof structures by causing a surcharge of local snow load on the lower roof and may pose a serious threat to pedestrians and vehicles on the ground. Therefore, it is of great significance to study the mechanism of snow sliding on roofs. Under the action of ambient temperature, solar radiation, internal heating of the building, etc., the bottom layer of roof snow is often presented in the form of porous ice after a complicated phase transition of the snow particles, under this circumstance, the interface between roof snow and roof can be seen as the contact between porous ice and roofing material. In order to investigate the initialization of roof snow sliding from the material point of view, the shear performance of the interface between different roofing materials and ice with different porosity was carried out in this study. Effects of different ambient temperatures (-4, -6, -8 ℃), different normal stress (0, 50, 100 kPa), and different ice porosity (represented by the contact area ratio of 1.0, 0.8, and 0.6) on this shear performance were analyzed by direct shear tests. Test results showed that the shear failure between ice and roofing material is brittle, and the interface shear strength is affected by the ambient temperature, normal stress, contact area ratio, as well as material type: the strength increases with the decrease of ambient temperature, the increase of normal stress, the increase of contact area ratio, and the increase of surface roughness of the material. Based on the test results, a quantitative relationship between the interface shear strength and the related factors was given in the article, which provides a useful reference for future experimental or simulation studies on roof snow sliding.